TAX INCOME AND GOVERNMENT REVENUE GENERATION IN NIGERIA: A COMPARATIVE ANALYSIS OF POST AND PRE IFRS ADOPTION (Journal of Global Accounting, 2022)
The need for an effective tax revenue mobilization as an alternative means of funds to the Nigerian Government has come to stay especially against the backdrop of uncertainty around global Oil prices raising the imperativeness of regular evaluation of how Tax income has contributed to resources available to Government for the benefit of her citizen, Flowing from this necessity, this study evaluates the impact of Tax income on Revenue Generation in Nigeria during the pre and post IFRS adoption. The period of the study comprises Eighteen years from 2003-2020 allowing a Nine year each for pre and post IFRS periods. Taxation is proxied by Value Added Tax and Petroleum Profit Tax, while Total Government Revenue represents Government Revenue. The data were obtained from the Federal Inland Revenue Service Tax Statistics and the Central Bank of Nigeria statistical Bulletin (2020). The study adopts a Three-model approach for clarity and concise presentation and analysis. The data were pretested with the aid of Descriptive Statistics, Pearson Correlation and Data normality test. The hypotheses were tested with the aid of Ordinary Least Square Regression method. The result shows that there is a significant difference between the impacts of Value Added Tax and Petroleum Profit Tax on Government Revenue in Nigeria during the dichotomous periods studied. The study recommends that the Tax Authorities should increase effort so that income from Tax should form a more substantial part of revenue accruing to the Government under the IFRS implementation in Nigeria.
Keywords: Government Revenue; International Financial Reporting Standards; Petroleum Profit Tax; Tax Income; Value Added Tax